2018
DOI: 10.1155/2018/2879793
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis of Anti‐Inflammatory and Antioxidant Effects of Mahonia aquifolium Flower and Fruit Extracts

Abstract: Oxidative stress and inflammation are interlinked processes. The aim of the study was to perform a phytochemical analysis and to evaluate the antioxidant and anti-inflammatory activities of ethanolic Mahonia aquifolium flower (MF), green fruit (MGF), and ripe fruit (MRF) extracts. Plant extract chemical composition was evaluated by HLPC. A DPPH test was used for the in vitro antioxidant activity. The in vivo antioxidant effects and the anti-inflammatory potential were tested on a rat turpentine oil-induced inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 86 publications
3
50
0
2
Order By: Relevance
“…The study by Vodnar and Socaciu [86] on the survival of probiotic bacteria belonging to L. casei and L. plantarum strains tested during storage at 4 • C demonstrated significantly higher numbers (p < 0.05) of survival bacteria encapsulated in chitosan-coated microspheres with selenium-enriched green tea (2 g/100 mL). These results, together with previous findings [84], suggest that immobilization of bacterial strains in Coatings 2019, 9,194 6 of 21 chitosan coating improve their viability during refrigeration storage. The chitosan exerts a protective effect on these living microorganisms and the microencapsulation with selenium-enriched green tea was complementary in maintaining the bacteria stability and increased their viability by storage at refrigeration temperature for 30 days.…”
Section: Effectiveness Of Improving Cell Survivalsupporting
confidence: 79%
See 2 more Smart Citations
“…The study by Vodnar and Socaciu [86] on the survival of probiotic bacteria belonging to L. casei and L. plantarum strains tested during storage at 4 • C demonstrated significantly higher numbers (p < 0.05) of survival bacteria encapsulated in chitosan-coated microspheres with selenium-enriched green tea (2 g/100 mL). These results, together with previous findings [84], suggest that immobilization of bacterial strains in Coatings 2019, 9,194 6 of 21 chitosan coating improve their viability during refrigeration storage. The chitosan exerts a protective effect on these living microorganisms and the microencapsulation with selenium-enriched green tea was complementary in maintaining the bacteria stability and increased their viability by storage at refrigeration temperature for 30 days.…”
Section: Effectiveness Of Improving Cell Survivalsupporting
confidence: 79%
“…In fact, encapsulation of probiotic bacteria with chitosan and alginate coating provides protection in simulated GI conditions, and it is a good way of delivering viable bacterial cells to the colon [37]. Considering the above, chitosan-coated alginate microspheres represents a good alternative for probiotic microorganism oral Coatings 2019, 9,194 5 of 21 delivery [82]. The chitosan-specific chemical structure allows important changes at the C-2 position with no difficulties [79].…”
Section: Chitosan-based Coating Microencapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of C. majus extract was determined as previously described, i.e., by high-performance liquid chromatography method coupled with mass spectrometry (HPLC-MS; Agilent Technology, Santa Clara, CA, USA) [45]. In this study, V. minor extract was characterized using a HPLC-DAD approach (Agilent Technology, Waldbronn, Germany), as described by Andreicut et al [95]. A Nucleosil 100 C18 column (240 mm × 4.6 mm, and 5 µm particle size) was used for chromatographic separation, from Macherey-Nagel (Duren, Germany).…”
Section: Chemical Composition Of Plant Extractsmentioning
confidence: 99%
“…Our previous work showed that MA flower extract contains 3 phenolic acids (chlorogenic acid, p-coumaric acid, ferulic acid) and 2 flavonoids (isoquercetin, rutin) (Andreicut et al, 2018).…”
Section: Experimental Designmentioning
confidence: 99%